SURVEY OF THE IMPACT OF THE COVID-19 PANDEMIC ON SMOKING BEHAVIOR IN ACEH - Septiani, Riza; Jannah, Miftahul; Laila, Nurnarita; Hasnur, Hanifah; Presilawati, Febyolla; Na’imah, Na’imah; Gusweni, Mira (Jukema (Jurnal Kesehatan Masyarakat Aceh), 2023)
Background: The COVID-19 pandemic has significantly impacted the decline in human quality of life across various aspects. The direct impact of the COVID-19 pandemic is evident in the health aspect, such as the high number of positive cases and deaths due to COVID-19. One of the groups considered vulnerable to Coronavirus infection is smokers.  This research aims to understand the impact of the COVID-19 pandemic on smoking habits and changes in smoking patterns, as well as smoking behavior (cigarette consumption, smoking areas, access, and ease of purchasing cigarettes) during the COVID-19 pandemic in Aceh. Method: This research employs descriptive analytics using a Cross-sectional approach. The sampling technique used in this study is Convenience/Accidental sampling with a sample of 255 respondents. The instrument used was an online survey in Google Form format distributed through WhatsApp, and the data were analyzed using Univariate analysis. Results: The survey indicates that concerning the intention to quit smoking, 22% of respondents stated that during the COVID-19 period, they had already tried to quit smoking, and another 48% of respondents intended to quit, although they had not succeeded yet. Based on the  number of cigarettes consumed, 54% of respondents had reduced smoking, and 26% of respondents intended to reduce but found it challenging. Regarding respondents' knowledge about cigarettes and COVID-19, 90% of respondents had good to fairly good knowledge about preventing the spread of COVID-19, 69% of respondents had received information from various media, with the majority receiving information from social media and print media. Concerning access to purchasing cigarettes, 77% of respondents directly purchased from stalls, shops, or local stores, and the majority bought cigarettes every day or every 2-3 days. In terms of respondents' perceptions of cigarettes and COVID-19, 22% of respondents stated that cigarettes were a risk factor for COVID-19, 1% considered cigarettes to be a protective factor, and 77% were undecided. Conclusion: The survey indicates a change in the  number of cigarettes consumed by respondents before and after the COVID-19 pandemic. Therefore, there is a need to  maximize of health promotion related to cigarettes and COVID-19, as well as strengthened the implementation of smoke-free areas (KTR - Kawasan Tanpa Rokok) and smoke-free homes. Consistent implementation of smoke-free areas is expected to improve public health, especially in controlling the risk factors for diseases and deaths caused by smoking and enhancing a healthy and clean living culture within society.